2021
DOI: 10.32607/actanaturae.11487
|View full text |Cite
|
Sign up to set email alerts
|

Nanobodies Are Potential Therapeutic Agents for the Ebola Virus Infection

Abstract: Ebola fever is an acute, highly contagious viral disease with a mortality rate that can reach 90%. There are currently no licensed therapeutic agents specific to Ebola in the world. Monoclonal antibodies (MAbs) with viral-neutralizing activity and high specificity to the Ebola virus glycoprotein (EBOV GP) are considered as highly effective potential antiviral drugs. Over the past decade, nanobodies (single-domain antibodies, non-canonical camelid antibodies) have found wide use in the diagnosis and treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
0
7
0
1
Order By: Relevance
“…The technique of Fc-fused single-domain antibody development was described previously (Godakova et al, 2019 ; Esmagambetov et al, 2021 ; Voronina et al, 2021 ; Favorskaya et al, 2022 ). The nucleotide sequence encoding B11-Fc antibody was synthesized at Evrogen Company (Moscow, Russia) and cloned into the pAAV–EGFP Control Vector plasmid instead of the EGFP gene at the EcoRI and XbaI restriction sites, thus obtaining the pAAV-B11-Fc plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of Fc-fused single-domain antibody development was described previously (Godakova et al, 2019 ; Esmagambetov et al, 2021 ; Voronina et al, 2021 ; Favorskaya et al, 2022 ). The nucleotide sequence encoding B11-Fc antibody was synthesized at Evrogen Company (Moscow, Russia) and cloned into the pAAV–EGFP Control Vector plasmid instead of the EGFP gene at the EcoRI and XbaI restriction sites, thus obtaining the pAAV-B11-Fc plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…There are several examples of human monoclonal antibody-based therapeutics against some botulinum toxin serotypes, which have demonstrated safety and efficacy and are currently at various stages of clinical research (Nowakowski et al, 2002 ; Fan et al, 2017 ; Rasetti-Escargueil et al, 2017 ; Garcia-Rodriguez et al, 2018 ; Snow et al, 2019 ; Matsumura et al, 2020 ). Along with monoclonal antibodies, studies are using single-domain antibodies (VHH) (Esmagambetov et al, 2021 ; Ryabova et al, 2021 ). Such antibodies can bind hard-to-reach antigenic epitopes through long parts of the variable chains - CDR3s.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated the construction methods and potential functions of nanobodies and summarized their recent progress in infectious diseases. component, P9-1 Nb-alkaline phosphatase; Nb-eGFP fusion Llauger et al (2021) NB7-14 Influenza H7N9 virus HA Bivalent Nb Gaiotto et al (2021) C5, H3, C1, F2 SARS-CoV-2 RBD Homotrimers Nb; VHH-Fc Huo J et al (2021) aEv6 Ebola Virus EBOV GP Nb-Fc Esmagambetov et al (2021) aRBD-2, aRBD-3, aRBD-5, aRBD-7, aRBD-41, aRBD-42, and aRBD-54…”
Section: Introductionmentioning
confidence: 99%
“…A P2C5-Fc recombinant antibody represents a P2C5 antibody fused with an Fc-fragment of human IgG1 enabling its dimerization. This modification can increase avidity and specific activity as well as circulation time of the molecule due to an increase in molecular weight and interaction with neonatal Fc receptor for IgG (FcRn) ( 21 ). The proposed recombinant Fc-fusion single-domain antibody variant may be more effective than a monoclonal antibody due to the presence of long CDR3 loops enabling their binding to conservative hard-to-reach epitopes of viral antigens.…”
Section: Discussionmentioning
confidence: 99%